Når stemmer brydes på nye måder: Lydbogsindlæsning af klassikere - Björkén-Nyberg, Cecilia (Passage - Tidsskrift for litteratur og kritik, 2020)
This article argues that Bakhtin’s concepts of heteroglossia and dialogic imagination are useful for theorising the process of transduction involved in the representation of the printed text in audiobook narration. The fact that new recordings of canonical novels keep being launched is regarded as a means of meeting listener’s urge to literally hear the past and of reconstructing the network of dialogic relations that is present in the original novels but it is also argued that there are pitfalls associated with this endeavour.